THU0614-HPR ASSESSING THE EFFECT OF INTERVENTIONS FOR AXIAL SPONDYLOARTHRITIS ACCORDING TO THE ENDORSED ASAS/OMERACT CORE OUTCOME SET: A META-RESEARCH STUDY OF TRIALS INCLUDED IN COCHRANE REVIEWS. (13th June 2020) - Asmussen Andreasen, R.; Kristensen, L. E.; Baraliakos, X.; Strand, V.; Mease, P. J.; De Wit, M.; Ellingsen, T.; Jensen Hansen, I. M.; Kirkham, J.; Wells, G.; Tugwell, P.; Maxwell, L.; et al.
Abstract : Background: The Assessment of SpondyloArthritis international Society (ASAS) has defined separate core sets for: i) symptom-modifying anti-rheumatic drugs (SM-ARD), ii) clinical record keeping, and iii) disease-controlling anti-rheumatic therapy (DC-ART). These all include the following domains: 'physical function', 'pain', 'spinal mobility', 'spinal stiffness' and 'patient global assessment' (PGA). The core set for clinical record keeping further includes the domains 'peripheral joints' and 'acute phase reactants', and the core set for DC-ART further includes the domains 'fatigue', 'spine/hip radiographs'. Objectives: To assess the effect of interventions for each of the 9 axSpA core domains. Methods: We investigated the efficacy across all interventions included in Cochrane reviews according to the core outcome set for axSpA, as reported in these eligible axSpA trials. We combined data using the standardized mean difference (SMD) to meta-analyze outcomes involving similar constructs. By meta-regression analysis, we examined the effect for each of the nine separate SMD measures on the primary endpoint across all trials. Results: Among 85 articles screened, we included 43 trials with 63 randomized comparisons. Mean (SD) number of core outcomes domains measured for SM-ARD trials was 4.2 (1.7). 6 trials assessed all 5 proposed domains. Mean (SD) for number of core outcome domains for DC-ART trials was 5.8 (1.7). Unfortunately, no trials assessed all 9 domains. 8 trials were judged to have high risk of selective outcome reporting. The most responsible core domains for achieving success in meeting the primary objective per trial were pain; OR (95% CI) 5.19 (2.28, 11.77) and PGA; OR (95% CI) 1.87 (1.14, 3.07). Conclusion: Overall outcome reporting was good for SM-ARD trials, and poor for DC-ART trials. None of the DC-ART trials assessed all 9 domains. Outcome-reporting bias and 'missing data' should be reduced by implementing the endorsed ASAS/OMERACT outcome domains in all clinical trials. Our findings suggest that PGA and pain likely provide a holistic assessment of disease beyond "objective measures" of spinal inflammation. Disclosure of Interests: Rikke Asmussen Andreasen: None declared, Lars Erik Kristensen Consultant of: UCB Pharma (Advisory Board), Sannofi (Advisory Board), Abbvie (Advisory Board), Biogen (Advisory Board), Speakers bureau: AbbVie, Amgen, Biogen, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Forward Pharma, Janssen Pharmaceuticals, MSD, Novartis, Pfizer, and UCB Pharma, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Vibeke Strand Consultant of: AbbVie, Amgen, Biogen, Celltrion, Consortium of Rheumatology Researchers of North America, Crescendo Bioscience, Eli Lilly, Genentech/Roche, GlaxoSmithKline, Hospira, Janssen, Merck, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Sanofi, UCB, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Maarten de Wit Grant/research support from: Dr. de Wit reports personal fees from Ely Lilly, 2019, personal fees from Celgene, 2019, personal fees from Pfizer, 2019, personal fees from Janssen-Cilag, 2017, outside the submitted work., Consultant of: Dr. de Wit reports personal fees from Ely Lilly, 2019, personal fees from Celgene, 2019, personal fees from Pfizer, 2019, personal fees from Janssen-Cilag, 2017, outside the submitted work., Speakers bureau: Dr. de Wit reports personal fees from Ely Lilly, 2019, personal fees from Celgene, 2019, personal fees from Pfizer, 2019, personal fees from Janssen-Cilag, 2017, outside the submitted work., Torkell Ellingsen: None declared, Inger Marie Jensen Hansen: None declared, Jamie Kirkham: None declared, George Wells: None declared, Peter Tugwell: None declared, Lara Maxwell: None declared, Maarten Boers: None declared, Kenneth Egstrup: None declared, Robin Christensen Grant/research support from: Dr. Christensen reports non-financial support from Board membership, grants from Consultancy (AbbVie, Amgen, Axellus A/S, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Eli Lilly, Hospira, MSD, Norpharma, Novartis, Orkla Health, Pfizer, Roche, Sobi, Takeda), personal fees from Employment (Research Unit for Musculoskeletal Function and Physiotherapy, Institute of Sports Science and Clinical Biomechanics, University of Southern Denmark), non-financial support from Expert testimony, grants from Grants/grants pending (Axellus A/S, AbbVie, Cambridge Weight Plan, Janssen, MSD, Mundipharma, Novartis, and Roche), grants from Payment for lectures including service on speakers bureaus (Abbott, Amgen, Axellus, Bayer HealthCare Pharmaceuticals, Biogen Idec, Bristol-Myers Squibb, Cambridge Weight Plan, Ipsen, Janssen, Laboratoires Expanscience, MSD, Mundipharma, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, Sobi, and Wyeth), grants from Payment for manuscript preparation (Axellus, Bristol-Myers Squibb, and Cambridge Weight Plan, Aleris-Hamlet (via Norpharma)), non-financial support from Patents (planned, pending or issued), non-financial support from Royalties, grants from Payment for development of educational presentations (Bristol-Myers Squibb, MSD, Pfizer), non-financial support from Stock/stock options, grants from Travel/accommodations/meeting expenses unrelated to activities listed (Abbott, AbbVie, Axellus, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Laboratoires Expanscience, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, and Wyeth), non-financial support from Other (err on the side of full disclosure), outside the submitted work; and I am involved in many health-care initiatives and research that could benefit from wide uptake of this publication (including Cochrane, OMERACT, IDEOM, RADS, and the GRADE Working Group). Musculoskeletal Statistics Unit, The Parker Institute is grateful for the financial support received from public and private foundations, companies and private individuals over the years. The Parker Institute is supported by a core grant from the Oak Foundation; The Oak Foundation is a group of philanthropic organizations that, since its establishment in 1983, has given grants to not-for-profit organizations around the world.., Consultant of: Dr. Christensen reports non-financial support from Board membership, grants from Consultancy (AbbVie, Amgen, Axellus A/S, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Eli Lilly, Hospira, MSD, Norpharma, Novartis, Orkla Health, Pfizer, Roche, Sobi, Takeda), personal fees from Employment (Research Unit for Musculoskeletal Function and Physiotherapy, Institute of Sports Science and Clinical Biomechanics, University of Southern Denmark), non-financial support from Expert testimony, grants from Grants/grants pending (Axellus A/S, AbbVie, Cambridge Weight Plan, Janssen, MSD, Mundipharma, Novartis, and Roche), grants from Payment for lectures including service on speakers bureaus (Abbott, Amgen, Axellus, Bayer HealthCare Pharmaceuticals, Biogen Idec, Bristol-Myers Squibb, Cambridge Weight Plan, Ipsen, Janssen, Laboratoires Expanscience, MSD, Mundipharma, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, Sobi, and Wyeth), grants from Payment for manuscript preparation (Axellus, Bristol-Myers Squibb, and Cambridge Weight Plan, Aleris-Hamlet (via Norpharma)), non-financial support from Patents (planned, pending or issued), non-financial support from Royalties, grants from Payment for development of educational presentations (Bristol-Myers Squibb, MSD, Pfizer), non-financial support from Stock/stock options, grants from Travel/accommodations/meeting expenses unrelated to activities listed (Abbott, AbbVie, Axellus, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Laboratoires Expanscience, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, and Wyeth), non-financial support from Other (err on the side of full disclosure), outside the submitted work; and I am involved in many health-care initiatives and research that could benefit from wide uptake of this publication (including Cochrane, OMERACT, IDEOM, RADS, and the GRADE Working Group). Musculoskeletal Statistics Unit, The Parker Institute is grateful for the financial support received from public and private foundations, companies and private individuals over the years. The Parker Institute is supported by a core grant from the Oak Foundation; The Oak Foundation is a group of philanthropic organizations that, since its establishment in 1983, has given grants to not-for-profit organizations around the world.., Speakers bureau: Dr. Christensen reports non-financial support from Board membership, grants from Consultancy (AbbVie, Amgen, Axellus A/S, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Eli Lilly, Hospira, MSD, Norpharma, Novartis, Orkla Health, Pfizer, Roche, Sobi, Takeda), personal fees from Employment (Research Unit for Musculoskeletal Function and Physiotherapy, Institute of Sports Science and Clinical Biomechanics, University of Southern Denmark), non-financial support from Expert testimony, grants from Grants/grants pending (Axellus A/S, AbbVie, Cambridge Weight Plan, Janssen, MSD, Mundipharma, Novartis, and Roche), grants from Payment for lectures including service on speakers bureaus (Abbott, Amgen, Axellus, Bayer HealthCare Pharmaceuticals, Biogen Idec, Bristol-Myers Squibb, Cambridge Weight Plan, Ipsen, Janssen, Laboratoires Expanscience, MSD, Mundipharma, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, Sobi, and Wyeth), grants from Payment for manuscript preparation (Axellus, Bristol-Myers Squibb, and Cambridge Weight Plan, Aleris-Hamlet (via Norpharma)), non-financial support from Patents (planned, pending or issued), non-financial support from Royalties, grants from Payment for development of educational presentations (Bristol-Myers Squibb, MSD, Pfizer), non-financial support from Stock/stock options, grants from Travel/accommodations/meeting expenses unrelated to activities listed (Abbott, AbbVie, Axellus, Biogen, Bristol-Myers Squibb, Cambridge Weight Plan, Celgene, Laboratoires Expanscience, Norpharma, Novartis, Pfizer, Roche, Rottapharm-Madaus, and Wyeth), non-financial support from Other (err on the side of full disclosure), outside the submitted work; and I am involved in many health-care initiatives and research that could benefit from wide uptake of this publication (including Cochrane, OMERACT, IDEOM, RADS, and the GRADE Working Group). Musculoskeletal Statistics Unit, The Parker Institute is grateful for the financial support received from public and private foundations, companies and private individuals over the years. The Parker Institute is supported by a core grant from the Oak Foundation; The Oak Foundation is a group of philanthropic organizations that, since its establishment in 1983, has given grants to not-for-profit organizations around the world.